Perbedaan Loneliness pada Remaja Laki-Laki dan Perempuan yang Kehilangan Ayah - Nenci Dorasma Uli Napitupulu; Ervina Marimbun Rosmaida Siahaan (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Losing a father, whether through death or divorce, is a significant life event that can impact adolescents' psychological well-being, one of which is feelings of loneliness. Fathers play a crucial role in a child's emotional and social development, and their absence can trigger feelings of isolation or a lack of social connection. This study aims to determine whether there are differences in levels of loneliness between male and female adolescents who have lost their fathers. This study used a quantitative approach with a comparative method. The subjects in this study were 152 adolescents, consisting of 96 female adolescents and 56 male adolescents who had lost their fathers. Data were collected using a loneliness scale structured according to aspects of loneliness. The data analysis technique used to test the hypothesis was an Independent Sample T-Test. The results of the data analysis showed a significance value (Sig. 2-tailed) of 0.105 (p > 0.05). This indicates that the hypothesis stating differences in levels of loneliness is rejected. Therefore, it can be concluded that there are no significant differences in loneliness experienced by male and female adolescents who have lost their fathers. Both gender groups showed relatively similar levels of loneliness in response to the loss of a father. The results of the data analysis showed a significance value (Sig. 2-tailed) of 0.105 (p > 0.05). This indicates that the hypothesis stating differences in levels of loneliness is rejected. Therefore, it can be concluded that there are no significant differences in loneliness experienced by male and female adolescents who have lost their fathers. Both gender groups showed relatively similar levels of loneliness in response to the loss of a father.